After the Revolution: State, Civil Society, and Democratization in Armenia and Georgia - Stefes, Christoph H.; Paturyan, Yevgenya J. (Frontiers in Political Science, 2021)
In 2003 and 2018, mass protests triggered the collapse of authoritarian regimes in Georgia and Armenia, respectively. In both cases, civil society organizations (CSOs) played an important role in laying the groundwork and organizing the protests. Following the toppling of semi-autocratic leaders, reform-oriented governments took over in both countries. Yet, the way civil society engaged the new rulers differed considerably. Whereas in Georgia, former civil society leaders were often absorbed into the new government, Armenian civil society has kept its distance from the new political leadership. In this paper, we attempt to explain why state-civil society relations after the revolutions have developed in different directions in these two Soviet successor states. We argue that three conditions explain differences in engagement with the new governments: CSOs pre-revolutionary cooperation with the political opposition, Western governments support for civil society before and after the political transitions, and the degree to which CSOs represent and are rooted in the general public. As a consequence, Georgia’s post-revolutionary regime lacked the checks and balances that CSOs usually provide, allowing it to sacrifice democratization on the altar of modernization. In Armenia, in contrast, CSOs have maintained a critical stance and continued to hold the government accountable.